Membantu Pelaksanaan Vaksinasi Covid di Desa Mandirancan, Banyumas - Putri Aminah Artika (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
Indonesia saw a continued increase in Covid cases from July to August 2021. The UNSOED thematic community service program (KKN) in Mandirancan Village, Banyumas, aimed to support Covid response efforts through vaccination assistance. This activity utilized the PLA and PRA methods, Participatory Village Assessment, and interviews to gather information. The program successfully increased the number of residents in Mandirancan Village receiving Covid vaccinations.